CHILD LABOR ISSUE AS DEPICTED IN ELIZABETH BARRET-BROWNING’S POEM THE CRY OF THE CHILDREN - Okki Irviana Nindi Astuti (Lexicon, 2013)
The Cry of the Children is a poem by Elizabeth Barret-Browning which was published in 1842. Through this poem, Elizabeth shows her objection to child labor in factories and mines in England. The bad conditions of those poor child labors, both physic and mental damages, are also demonstrated in The Cry of the Children. Elizabeth uses the right dictions which can show that child labor issue happened in England during the Industrial revolution and also the miserable life the poor children had to endure.